2010
DOI: 10.12693/aphyspola.117.640
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophes and Chaos in Business Cycle Theory

Abstract: The primary thesis of this paper is that a nonlinear dynamical systems theory provides a basis for conducting all kinds of comparisons in the theory of business cycles, and it also enables its further development. A cognitive aim was to show that applying the theory of bifurcations and morphogenesis in the domain of economic fluctuations allows us to construct models of the cycle with greater explicatory and utility values than there were so far. In this way, the precision and consistency of the theory increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…Hartelman et al [11,12] and Wagenmakers [13] found direct relation between probability density function f (y) associated with Eq. (8) and that corresponding to an asymptotic stationary stochastic process f s (y). They proved that f (y) and f s (y) converge over time assuming fast thermalization of the system, that is assuming much faster changes in the system state than in the control variables.…”
Section: Cusp Catastrophe Modelmentioning
confidence: 99%
“…Hartelman et al [11,12] and Wagenmakers [13] found direct relation between probability density function f (y) associated with Eq. (8) and that corresponding to an asymptotic stationary stochastic process f s (y). They proved that f (y) and f s (y) converge over time assuming fast thermalization of the system, that is assuming much faster changes in the system state than in the control variables.…”
Section: Cusp Catastrophe Modelmentioning
confidence: 99%
“…It is therefore an open system showing emergence. This conclusion can be justified on the basis of the catastrophe theory, which is a method of classifying stable forms [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…The model is so related to variables as the temperature, the energy and the mass, the weight of the various states (at quantum level), which, "mutatis mutandis", are very important in a lot of economic processes too, from economic geography and gravity models for economy, to economic behaviours treated with game theory [35], eco- nomic analogies to thermodynamics and chaos in business cycle theories [36,37].…”
Section: T  V Vmentioning
confidence: 99%